Customers satisfaction towards Kedai Rakyat 1 Malaysia (KR1M), G-Mart Supermarket and The Store Pacific Milimewa in Inanam, Sabah / Esther Nelly Joseph and Harbiah Hamsya - Joseph, Esther Nelly; Hamsya, Harbiah (2013)
One of the key components of organization sustainability is a customer satisfaction. This study was conducted to examine customer satisfaction towards KR1M, G-Mart and Milimewa Superstore in Inanam town. 150 of questionnaires have been distributed to the selected superstores. The finding shows that there are four catalysts have been identified as the factors that contribute to the customer satisfaction which is location, price, quality of product and counter service. Counter service is the most influential factor that contributes to the customer satisfaction. KR1M have been identified as the most preferred convenience store by the customer based on the factors given. Continuous improvement should be practice in order to increase the customer satisfaction.